Pemberian Minyak Telon dalam Upaya Mencegah Perut Kembung pada Bayi Baru Lahir - Gina Permatasari; Nining Hening Pramesti; Sri Mulyani Nurhayati (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2020)
The purpose of this study was to determine the administration of telon oil to newborns to prevent flatulence. This type of research is simple descriptive with a case study approach. The results of the investigation to the two research subjects, namely By. Mrs. A on the first day before giving telon oil 29 cm circumference of the abdomen, with a soft stomach, not moving much, not crying often without cause, and after conducting research Research Subject I did not occur bloating. Still, on the third day, the stomach is a bit hard. In conclusion, when carrying out the assessment of the baby has a gestation period following the inclusion criteria and intervene in giving telon oil using telon oil on the baby's stomach. Keywords: Newborns, Telon Oil, Flatulence